Pengaruh Motivasi Terhadap Kinerja Tenaga Kependidikan Perguruan Tinggi Vokasi di Majalengka - Pamela, Karim; Khusni, Khusni (Jurnal Inovasi Bisnis Manajemen dan Akuntansi, 2024)
Using a case study at the YPIB Majalengka Nursing Academy, the purpose of this study was to identify and analyze the effect of motivation on the performance of education personnel at Vocational Colleges in Majalengka. This study used 21 saturated samples. Quantitative methods process data from questionnaires before being converted into numerical data using a Likert scale. The results of the work motivation coefficient table show that the t-score value is 2.163> ttable 1.708 and a significant value of 0.040 <0.05, so Ha is accepted and H0 is rejected, indicating that motivation has an effect. The results showed that motivation has a significant impact on the performance of employees of the YPIB Majalengka Nursing Academy. A high level of motivation indicates a need for achievement, which means that high motivation will be essential to improve employee performance at Majalengka Vocational College.